2019
DOI: 10.1155/2019/5847040
|View full text |Cite
|
Sign up to set email alerts
|

Role of Resveratrol on Indoxyl Sulfate-Induced Endothelial Hyperpermeability via Aryl Hydrocarbon Receptor (AHR)/Src-Dependent Pathway

Abstract: Resveratrol (RES), a dietary polyphenol compound, has been shown to possess health benefits due to its anti-inflammatory, antioxidative, and antiatherosclerosis properties. Tryptophan metabolite-derived indoxyl sulfate (IS) is identified as one of the uremic toxins and physiological endogenous ligand/activator of aryl hydrocarbon receptor (AHR), associated with atherosclerosis in chronic kidney disease (CKD) patients. Studies have shown that a high serum level of IS causes deleterious effects on health primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…However, Chen et al [ 75 ] recently demonstrated that PCS increased phosphorylation of VE-cadherin at tyrosine 658 (Y658) in HUVECs. In a similar manner, Assefa et al [ 78 ] found that IS increased VE-cadherin phosphorylation in bovine aortic endothelial cells (BAECs). VE-cadherin phosphorylation is mediated by tyrosine kinases, such as Src, and is associated with enhanced endothelial permeability, possibly by inducing VE-cadherin internalization [ 81 ].…”
Section: Endothelial Dysfunction In Ckdmentioning
confidence: 76%
See 3 more Smart Citations
“…However, Chen et al [ 75 ] recently demonstrated that PCS increased phosphorylation of VE-cadherin at tyrosine 658 (Y658) in HUVECs. In a similar manner, Assefa et al [ 78 ] found that IS increased VE-cadherin phosphorylation in bovine aortic endothelial cells (BAECs). VE-cadherin phosphorylation is mediated by tyrosine kinases, such as Src, and is associated with enhanced endothelial permeability, possibly by inducing VE-cadherin internalization [ 81 ].…”
Section: Endothelial Dysfunction In Ckdmentioning
confidence: 76%
“…Loss of endothelial integrity and enhanced permeability are also seen in the aortic endothelium of nephrectomized rats, an animal model of CKD [ 76 , 77 ]. In vitro, PCS, IS, and uremic serum reduced the transendothelial electrical resistance (TEER), which indicates an increase in endothelial permeability [ 75 , 78 , 79 ]. In this regard, studies have also found that uremic toxins induced F-actin cytoskeletal remodeling in endothelial cells, leading to changes in cell morphology [ 13 , 79 , 80 ].…”
Section: Endothelial Dysfunction In Ckdmentioning
confidence: 99%
See 2 more Smart Citations
“…Some evidence from previous reports has shown that RSV efficiently limits the induction of CYP1A1 via the AhR ligand [ 55 ]. In our data, we obtained a similar result, showing that RSV treatment can block the elevation of CYP1A1 and CYP1B1 in protein and mRNA levels induced by IS ( Figure 3 A–D).…”
Section: Discussionmentioning
confidence: 99%